Level of Shooting Ability in Football Games at the Long Gathering Club, Padang Guci Hilir, Kaur Regency - Megi Personi; Deffri Anggara (Penerbit Jurnal Indonesia, 2023)
This study aims to determine the ability to shoot in a soccer game at Padang Guci Hilir Long Gathering, Kaur Kaur District. This type of research is a qualitative descriptive research. The research sample is 25 people. The instrument used in this study was the Football shooting test. Where the results of the level of shooting ability in soccer games at the Padang Guci Hilir Gathering in Padang Guci Hilir Regency in this study show the classification of